Evaluation of arsenic, selenium, tin and mercury in water and sediments of Bitter Lakes, Suez Canal, Egypt - Mohamed A. El-Sawy; L.I. Mohamedein; Kh.M. El-Moselhy (Egyptian Journal of Aquatic Research, 2023)
Surface water and surface sediment samples were collected from Bitter Lakes from winter to autumn 2018 to evaluate the impact of land-based activities on the distribution of arsenic (As), selenium (Se), tin (Sn), and mercury (Hg). The metal concentrations were measured in 12 sampling sites along Bitter Lakes in the Suez Canal by the hydride system MH10 coupled with an atomic absorption spectrophotometer. The most industrialized regions in the lake showed elevated levels of metals in the water and sediments compared to other studied areas. As, Sn, and Hg showed the highest levels in water during winter (9.66, 1.03, and 0.25 µg/l, respectively), while Se recorded its highest values during summer (2.60 µg/L). Similarly, the highest total concentrations of the investigated elements in the sediments were 22400.00, 605.85, 40.91, and 446.55 ng/g, respectively.